c.3 - Beckerman, Wilfred (New Delhi, 1984)
This book covers four main topics: national accounting concepts and conventions; elementary macroeconomics; income distribution; and comparisons of national product over time and space. The treatment of the first two topics includes simple numerical exercises. In this way, as with arithmetic textbooks, the reader can see for himself whether he has really understood the text, and can acquire some facility at dealing with the problems covered. The whole argument is also supported by extensive use of diagrams and practical illustrations. In this third edition the discussion of the distribution of income has been greatly expanded and a new chapter (Chapter 8) added accordingly.
Keywords: Income distribution